Pemberdayaan Forum Pemuda Lintas Agama (FPLA) dalam Penguatan Kapasitas Anggota Sebagai Aktor Penggerak Toleransi di Kabupaten Kulon Progo Yogyakarta - M. Syafi’ie; Alif Lukmanul Hakim; Despan Heryansyah (Wisanggeni : Jurnal Pengabdian Masyarakat, 2021)
Indonesia is a country built on the foundation of multiculturalism. Since the beginning, the founders of this Republic were aware of this, so that the first principle of Pancasila reads God Almighty. This is an important indication that Indonesia is not a religious state, all religions before the state have the same and equal position. The state, in fact, guarantees all citizens to be free to worship according to their respective religions and beliefs. However, the life of the nation, state and society in a concrete sense is not always as good as it is conceived. In practice, religious primordialism, religious fundamentalism, and even radicalism still frequently occur. According to certain religious teachings, this group isolates, or even is hostile to, adherents of other different religions. The forms of this movement vary, from the most violent in the form of acts of terrorism, to the most gentle in the form of rejection of other parties who are different. Young people who have just entered high school and university are easy targets of this movement. Whereas in fact, the Indonesian nation from a cultural historical aspect, is a nation that loves harmony, a nation that respects and respects differences, united in the spirit of mutual cooperation. However, the spirit or soul is often covered by the massive fundamentalism movement carried out by this particular group. Therefore, departing from the above problems, we are collaborating with the Kulon Progo Interfaith Youth Forum (Forum Pemuda Lintas Agama) to organize activities that can foster unity and tolerance, especially among youth in Kulon Progo. Kulon Progo is used as an object because it is in a transition period to become an urban area, which of course there will be many identity intersections in the community. The activity was successfully held for two online discussions. The first discussion discussed tolerance and harmony between religions in a more general context. How is the situation in the world and in Indonesia itself.This was followed by a second discussion by presenting representatives from several religions, to convey the perspective of tolerance from their respective religious teachings. Keyword: Interfaith, Tolerance, Youth